2022
DOI: 10.1155/2022/2133712
|View full text |Cite|
|
Sign up to set email alerts
|

A New Decision-Making GMDH Neural Network: Effective for Limited and Fuzzy Data

Abstract: This paper presents a new approach to solve multi-objective decision-making (DM) problems based on neural networks (NN). The utility evaluation function is estimated using the proposed group method of data handling (GMDH) NN. A series of training data is obtained based on a limited number of initial solutions to train the NN. The NN parameters are adjusted based on the error propagation training method and unscented Kalman filter (UKF). The designed DM is used in solving the practical problem, showing that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Elevating Swarm Efficiency via Neural Networks and Reinforcement Learning In a bid to optimize the potential of UAV swarms, the experiment in the article uses an additional layer of sophistication. This method has been already used in other experiments [3], but not yet in UAV swarms. Building upon the foundation of heterogeneous UAV swarms, an advanced layer is injected into the equation: the fusion of neural networks and reinforcement learning.…”
Section: Introductionmentioning
confidence: 99%
“…Elevating Swarm Efficiency via Neural Networks and Reinforcement Learning In a bid to optimize the potential of UAV swarms, the experiment in the article uses an additional layer of sophistication. This method has been already used in other experiments [3], but not yet in UAV swarms. Building upon the foundation of heterogeneous UAV swarms, an advanced layer is injected into the equation: the fusion of neural networks and reinforcement learning.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%